Knockdown of Cytochrome P450 Genes Gh_D07G1197 and Gh_A13G2057 on Chromosomes D07 and A13 Reveals Their Putative Role in Enhancing Drought and Salt Stress Tolerance in Gossypium Hirsutum - Magwanga, Richard Odongo; Lu, Pu; Kirungu, Joy Nyangasi; Dong, Qi; Cai, Xiaoyan; Zhou, Zhongli; Wang, Xingxing; Hou, Yuqing; Xu, Yanchao; Peng, Renhai; Agong, Stephen Gaya; Wang, Kunbo; et al. (Multidisciplinary Digital Publishing Institute, 2019)
We identified 672, 374, and 379 CYPs proteins encoded by the CYPs genes in Gossypium hirsutum, Gossypium raimondii, and Gossypium arboreum, respectively. The genes were found to be distributed in all 26 chromosomes of the tetraploid cotton, with chrA05, chrA12, and their homeolog chromosomes harboring the highest number of genes. The physiochemical properties of the proteins encoded by the CYP450 genes varied in terms of their protein lengths, molecular weight, isoelectric points (pI), and even grand hydropathy values (GRAVY). However, over 99% of the cotton proteins had GRAVY values below 0, which indicated that the majority of the proteins encoded by the CYP450 genes were hydrophilic in nature, a common property of proteins encoded by stress-responsive genes. Moreover, through the RNA interference (RNAi) technique, the expression levels of Gh_D07G1197 and Gh_A13G2057 were suppressed, and the silenced plants showed a higher concentration of hydrogen peroxide (H2O2) with a significant reduction in the concentration levels of glutathione (GSH), ascorbate peroxidase (APX), and proline compared to the wild types under drought and salt stress conditions. Furthermore, the stress-responsive genes 1-Pyrroline–5-Carboxylate Synthetase (GhP5CS), superoxide dismutase (GhSOD), and myeloblastosis (GhMYB) were downregulated in VIGS plants, but showed upregulation in the leaf tissues of the wild types under drought and salt stress conditions. In addition, CYP450-silenced cotton plants exhibited a high level of oxidative injury due to high levels of oxidant enzymes, in addition to negative effects on CMS, ELWL, RLWC, and chlorophyll content The results provide the basic foundation for future exploration of the proteins encoded by the CYP450 genes in order to understand the physiological and biochemical mechanisms in enhancing drought and salt stress tolerance in plants.
Keywords: cytochrome P450 genes; virus-induced-gene-silencing; oxidant and antioxidant enzymes; stress-responsive genes; drought and salt stress